Extended-window decorrelating detector for asynchronous CDMA channels and its performance analysis. - Seung Maeng (IEEE Transactions on communications)
We propose a new decorrelating detector for the asynchronous code-division multiple-access channels, called the extended-window decorrelating detector (EW-DD). The EW-DD helps to avoid the noncausality problem of the filter-type decorrelating detector and achieve a simplified detection by converting the asynchronous system into the synchronous one. It also helps to enhance the bit-error rate (BER) performances by utilizing one whole period of information of all users and by eliminating the multiple-access interference from the past data through feedback. Nevertheless, the computational complexity is kept lower than that of other existing decorrelating detectors. We carry out BER analysis of the EW-DD and demonstrate performance improvements of the EW-DD over other decorrelating detectors through computer simulations